Kemampuan Zeolit Dan Kulit Ubi Kayu Untuk Memperbaiki Kadar Besi (Fe) Dan pH Air Sumur Bor - Mutia Wahdini; Munawar Raharja; Syarifudin A.; Zulfikar Ali As (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
The amount of Fe in groundwater is usually quite high and causes the water to turn yellow-brown in color. According to preliminary test results, Fe levels were 4.62 mg/L and pH was 4.3 in one of the drilled wells in Banjarbaru, which did not fulfill quality criteria. Using zeolit and cassava peel to enhance Fe levels can be taken as an option. The aim of this study was to determine the effectiveness of the combination of zeolite and cassava peel in improving Fe and pH levels in a drilled water well. An experiment with a post-test only control group design was used for this study. The research population was the entire water supply from one of Banjarbaru’s drilled wells. The research sample was drilled well water, which was taken in part for testing. The Kruskal-Wallis test was employed to analyze differences in Fe levels, followed by the Mann Whitney test with a p-value < 0.05, indicating that there is a significant difference in Fe levels after treatment with combinations A, B, and C. According to the study’s findings, combinations C were the most effective in increasing the Fe levels and pH of drilled well water by up to 0.91 mg/L (78.32%) and 7.2.